IDARP: ID-based Address Resolution Protocol - Lone, Imtiyaz Ahmad; Ali, Jahangeer; Lone, Kalimullah (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper, security attacks in ARP are classified and logically organized/represented in a more lucid manner.ARP provides no authentication mechanism to the incoming request packets this is the reason that any client can forge an ARP message contains malicious information to poison theÂ ARP cache of target host. There are many possible attacks on ARP which can make the communication unsecure such as man-in-the-middle (MITM), Denial of service (DOS) and cloning attack.